The Relationship between Coping Styles and Psychological Well-being of Women Heads of Households - Maedeh Asgharpour; Soheil Moazami Goudarzi (Journal of Modern Psychology, 2024)
Objective: The present study was conducted with the aim of investigating the relationship between coping styles and psychological well-being in female heads of households.Methods: The research design was quantitative, descriptive and within the framework of the correlational method. The statistical population of the research was formed by all the women heads of the household in Sarai, Yousef Abad neighborhood of Tehran in 2024. In this study, using convenience sampling, 50 women were selected as samples. In order to collect research data, Coping Styles Questionnaire for Stressful Situations (CISS) and Ryff scale of psychological well-being (RSPWB) were used. The collected data were analyzed using SPSS-26 software, and research hypotheses and data were analyzed using correlation test, one-sample t, one-factor ANOVA, and Tukey's post hoc test.Results: The results showed that there is a significant positive relationship between problem-oriented coping style and psychological well-being in women heads of households. Also, there is a significant negative relationship between emotional and avoidant coping styles with psychological well-being. According to (P<0.01) for all hypotheses, the level of significance has been proven.Conclusion: Therefore, it can be concluded that female heads of households who use a problem-oriented coping style have a greater sense of self-efficacy and peace of mind, and the use of previous experiences in solving various life problems will make them self-reliant people. And they have higher psychological well-being, and in contrast to female heads of households who use an emotional and avoidant coping style, they have lower psychological well-being.